GPS-GSM Modem Application as Car Position and Fuel Monitoring System - Ahmad Taqwa; Masayu Anisah; Evelina Evelina; Sabilal Rasyad; Amperawan Amperawan (IAES Indonesia Section, 2015)
problems delay delivery of fuel to gas stations is still difficult to predict. This raises concerns of distributors. We also difficult to know the contents of the tank as it was stolen during the trip. This study aims to resolve the issue. By utilizing GPS, GSM modem and ultrasonic sensors we can know the location and position of the car in detail, and to determine the volume of fuel in the tank. We use google maps that created with Delphi program